Exploring the Association of Sociodemographic Factors and Primary Diagnosis With Transition Readiness in Adolescents With Rheumatic Disease - Maryem Al Manaa; Yuhan Ma; Chan‐hee Jo; Una E. Makris; Nicole Bitencourt; Tracey Wright; Lorien Nassi (ACR Open Rheumatology)
Objective Transitioning from pediatric to adult care is challenging for adolescents with chronic health conditions. The Transition Readiness Assessment Questionnaire (TRAQ) is a validated tool for measuring transition readiness in pediatric patients with chronic diseases. This study examines the association of sociodemographic factors and primary diagnosis with transition readiness in adolescents with rheumatic disease using TRAQ scores. Methods We conducted a retrospective chart review of 882 adolescents with rheumatic diseases, aged 14 to 19 years, from September 2019 to December 2021. TRAQ scores, primary diagnosis, and demographic characteristics were collected. Bivariate and multiple linear regression analyses were used to identify predictors of transition readiness. Results We collected 882 TRAQs. Lupus diagnosis was significantly associated with higher TRAQ scores, whereas juvenile dermatomyositis diagnosis negatively influenced transition readiness. Non‐Hispanic ethnicity correlated with higher scores in managing medications and tracking health issues, and male gender was significantly linked to lower scores in tracking health issues and managing daily activities. There was no association between TRAQ scores and age, race, primary language of the parent, insurance type, median household income, and suicidality screen. A total of 118 patients completed two TRAQs with a mean interval of 13.5 months. There was no significant change in TRAQ scores over time. However, Hispanic patients, patients with Spanish‐speaking parents, and patients with lupus scored higher on the second TRAQ. Conclusion In our cohort, transition readiness varied by primary diagnosis. Transition plans tailored to the needs of vulnerable adolescents are required to enhance health management skills and facilitate a successful transition.